Analysis of Carbon Emission Calculation on Converted Electric Vehicles to Determine Emission Reduction Potential: Review - Ikwal, Ahmad; Pranoto, Hadi (Universitas Muhammadiyah Yogyakarta, 2025)
The transportation sector is a major contributor to carbon emissions in Indonesia, mainly due to the widespread use of fossil fuel-powered vehicles. To lessen these environmental impacts, converting conventional motor vehicles into electric vehicles is seen as an effective and cost-efficient solution. This study aims to examine the potential for reducing carbon emissions through the conversion to electric cars by reviewing national journals and conducting simple simulations. The research used a systematic literature review approach, comparing annual emissions of fossil fuel vehicles (Internal Combustion Engine/ICE) and electric vehicles (EV) based on energy consumption and yearly mileage. Results indicate that the potential for emission reduction ranges from 0.0036% to over 85%, with an average of around 37%, with the highest reductions observed in scenarios where renewable energy sources dominate. Simulations demonstrate that vehicle conversion can cut emissions by approximately 29% for an annual mileage of 10,000 km. The success of emission reduction depends heavily on the composition of the national electricity mix, which is still largely dominated by PLTU. Increasing the renewable-energy share to 50% could significantly boost emission reductions.